Giant Thermal Expansion in 2D and 3D Cellular Materials. Issue 18 (25th March 2018) - Zhu, Hanxing; Fan, Tongxiang; Peng, Qing; Zhang, Di
Abstract: When temperature increases, the volume of an object changes. This property was quantified as the coefficient of thermal expansion only a few hundred years ago. Part of the reason is that the change of volume due to the variation of temperature is in general extremely small and imperceptible. Here, abnormal giant linear thermal expansions in different types of two‐ingredient microstructured hierarchical and self‐similar cellular materials are reported. The cellular materials can be 2D or 3D, and isotropic or anisotropic, with a positive or negative thermal expansion due to the convex or/and concave shape in their representative volume elements respectively. The magnitude of the thermal expansion coefficient can be several times larger than the highest value reported in the literature. This study suggests an innovative approach to develop temperature‐sensitive functional materials and devices. Abstract : Single‐level or hierarchical cellular materials can be two‐dimensional or three‐dimensional, isotropic or anisotropic, and have a positive or negative coefficient of linear thermal expansion due to the convex or/and concave shape in their representative volume elements (RVEs). The magnitude of the thermal expansion coefficient could be several times larger than the highest value reported in the literature.